(untitled) (Revista Contexto & Educação, 2020)
A research group made of Elementary and High School students of a private school located in Rio do Sul (SC) could experience the contribution and acts provided by the Scientific Research - SR - in Brazil. The data was collected from bibliography researches and observation. For better analysis, this group was split into two: distancing and approachment among the SR group and principles of the SR institutionalized in Brazil. The data shows there are distancing and approachment in this group when it goes to concept and the activities themselves, however the greater is the distancing in the conceptions. It is easy to agree that these activities and conceptions contribute positively to accomplish the scheduled researches.